(untitled) (Ustozlar uchun, 2025)
This article explores how corpus linguistic methods are applied in stylistic analysis to investigate the linguistic features of literary texts. Corpus stylistics combines quantitative techniques from computational linguistics with qualitative literary interpretation, allowing scholars to identify patterns in language use, such as word frequency, collocation, and concordance. The study highlights how corpus methods provide objective evidence for stylistic interpretation and help researchers describe authors’ unique linguistic choices. Examples from English prose and poetry demonstrate that corpus-based stylistics not only enhances accuracy in analysis but also bridges the gap between linguistic science and literary art.